Effects of different antibacterial disinfectants on microleakage of bulk-fill composite bonded to different tooth structures. - Bin-Shuwaish, Mohammed.; AlHussaini, Alhanouf.; AlHudaithy, Lina.; AlDukhiel, Shamma.; AlJamhan, Abdullah.; Alrahlah, Ali. (Tufts University. Tisch Library., 2021)
Keywords: Microleakage, 2% chlorhexidine, Listerine Miswak, Bulk fill, Resin composite, Antibacterial cavity disinfectants, Class V.; Springer Open.